2020
DOI: 10.1007/s11292-020-09428-9
|View full text |Cite
|
Sign up to set email alerts
|

A simple checklist, that is all it takes: a cluster randomized controlled field trial on improving the treatment of suspected terrorists by the police

Abstract: Objectives When it comes to interviewing suspected terrorists, global evidence points to harsh interrogation procedures, despite the likelihood of false positives. How can the state maintain an effective counterterrorism policy while simultaneously protecting civil rights? Until now, the shroud of secrecy of "national security" practices has thwarted attempts by researchers to test apparatuses that engender fair interrogation procedures. The present study aims to test one approach: the use of a "procedural jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…As this study shows, police call backs as opposed to the standard care would be an improved level of service, which would potentially increase future cooperation. At the same time, we did not follow up on our treatment victims to understand whether they do engage with the police again more than control participants – a common limitation in experiments of this nature (see Langley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this study shows, police call backs as opposed to the standard care would be an improved level of service, which would potentially increase future cooperation. At the same time, we did not follow up on our treatment victims to understand whether they do engage with the police again more than control participants – a common limitation in experiments of this nature (see Langley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It then follows that the satisfaction of victims who report crime is shaped by the reporting and subsequent investigation process; however, there is a demonstrated link between victim-initiated contact and dissatisfaction with law enforcement (Bradford, 2010;Jackson et al, 2012;Lee et al, 2019). The magnitude of this dissatisfaction is dependent on the services that officers provide (Jackson et al, 2012) and the manner in which they treat citizens (Bradford, 2010;Bradford et al, 2009;Langley et al, 2021;Laxminarayan et al, 2013;Tankebe, 2009).…”
Section: Victim Satisfaction With Police Performancementioning
confidence: 99%
“…This has created fertile ground for testing new approaches in policing, including behaviourally informed interventions. For example, in a cluster RCT with 65 teams of counter-terrorism officers at borders, Langley et al (2021) found that the use of a checklist significantly increased suspects' perceptions of police legitimacy along several dimensions.…”
Section: Limited Empiricismmentioning
confidence: 99%
“…These include improvements in police attitudes and behaviors, as well as public perceptions of the police (Antrobus et al, 2019;Rosenbaum & Lawrence, 2017;Skogan et al, 2015;Weisburd et al, 2022;Wood et al, 2020). Finally, randomized field trials have tested the effects of procedural justice interventions carried out by police officers during two types of encounters: traffic stops (Mazerolle et al, 2012(Mazerolle et al, , 2013Sahin et al, 2017), and interrogations of terrorism suspects (Langley et al, 2021). These studies showed that procedural justice interventions were associated with a variety of advantageous effects on attitudes and behavioral intentions.…”
Section: Procedural Justicementioning
confidence: 99%